Radiotherapy for gynecologic cancer in nonagenarian patients: a framework for new paradigms. Issue 1 (9th May 2016) - Méry, Benoîte; Ndong, Sylvie Mengue; Guy, Jean‐Baptiste; Assouline, Avi; Falk, Alexander T.; Valeille, Anaïs; Trone, Jane‐Chloé; Rivoirard, Romain; Auberdiac, Pierre; Vallard, Alexis; Espenel, Sophie; Moriceau, Guillaume; et al.
Abstract: No consensus exists regarding the role of radiotherapy in the management of gynecologic cancer in nonagenarian patients. We retrospectively reviewed the outcomes of 19 consecutive nonagenarian patients with gynecologic cancer (6 endometrial cancers, 6 cervical cancers, 4 vulvar cancers, and 3 vaginal cancers) who were treated with radiotherapy. Radiotherapy was performed mainly in a palliative setting ( n = 12; 63.2%), with a median dose of 45 Gy (range, 6–76 Gy). Infrequent major acute or late toxicities were reported. Among 19 patients, 9 (47.4%) experienced tumor progression, 5 (26.3%) experienced complete response, 2 (10.5%) experienced stable disease and/or partial response. At last follow‐up, 12 patients (63.2%) had died; most deaths ( n = 9) occurred because of the cancer. These results suggest that radiotherapy is feasible in the treatment of nonagenarian patients with gynecologic cancer.